Immigration vs. Poverty: Causal Impact on Demand for Redistribution in a Survey Experiment - Lisa Windsteiger; Andrea Martinangeli (ZBW - Leibniz Information Centre for Economics, 2020)
In a survey experiment conducted in Germany, we investigate how preferences over both the financing and the provision of redistributive policies are affected by poverty and immigration. We find that while information about poverty has no detectable impact on the progressivity of the respondents' demanded income tax schedule, information about immigration has a sizeable and signi ficant negative impact for middle income respondents. The opposite holds for low income earners, such that effects cancel out at the aggregate level. On the provision side, middle income respondents see public education as a viable response to both poverty and immigration, while low income respondents desire less public expenditure on education due to immigration. These heterogeneities suggest that understanding the relationship between immigration, poverty and demand for redistribution and addressing its pitfalls requires in-depth investigations by population segment.
Keywords: D31; D63; H53; J15; 330; Immigration; poverty; redistribution; survey experiment